Development of a boronic acid sensor-based glucose-responsive nanoparticulate insulin delivery system - Siddiqui, Nabil Ahmad (2017)
Diabetes is one of the most common chronic diseases in the world and its incidence is on the rise. Maintenance of continuous normoglycaemic conditions is the key goal for the management of both type 1 and type 2 diabetes in patients. Glucose responsive insulin delivery (GRID) systems have the potential to act as artificial pancreas as they can modulate the insulin release relative to external glucose concentrations. GRIDs can not only achieve tighter glycaemic control by preventing both hypo- and hyperglycaemia, but also eliminate the need for frequent finger-stick glucose tests and multiple daily insulin injections. In this research, we examined the selectivity of and insulin release from two boronic acids (2-formyl-3-thienylboronic acid (FTBA) and 4-formylphenylboronic acid (FPBA)) to glucose when conjugated to chitosan as nanoparticles. Adsorption of glucose to BA: chitosan conjugates was dose-dependent up to 1:1 at 35 and 42% for FPBA and FTBA respectively but the FTBA conjugates adsorbed more glucose and fructose at respective FPBA ratios. The affinity of both BA conjugates to glucose decreased with increase in BA ratio. On the other hand, the affinity of both BA conjugates for fructose decreased from ratio 1:1 to 2:1 then rose again at 3:1. Insulin release from FPBA nanoparticles (FPBAINP) and FTBA nanoparticles (FTBAINP) were both concentration-dependent within glyceamically relevant values (1-3mg/ml glucose and 0.002mg/ml fructose). Furthermore, the total amounts of insulin released from FPBAINP in both the media were higher than from FTBAINP. Both FPBAINP and FTBAINP have the potential for development as a glucose-selective insulin delivery system in physiological settings.